MODALIZAÇÕES AUTONÍMICAS COMO MARCAS DE SUBJETIVIDADE EM PROCESSOS DE CRIAÇÃO - Calil, Eduardo (Intercâmbio, 2010)
This work aims to describe and analyse marks of autonymie and autonymous modalization (Authier-Revuz) left in written and oral texts by schoolars of 2nd grade of elementary school. For this, practical of textualization in classroom were filmed when the pupils, organized in pairs, would have to combine and write an only text.